Szukanie ojczyzny - Milosz, Czeslaw (Krakow : Wydawn. Znak, 1992)
Autobiography of the Polish author focusing on his childhood in Lithuania.
Includes index.
Keywords: Milosz, Czeslaw -- Homes and haunts -- Lithuania -- Vilnius; Milosz, Czeslaw -- Childhood and youth; Authors, Polish -- 20th century -- Biography; Vilnius (Lithuania) -- Civilization; Lithuania -- Civilization